Effect of the buffer layer on the magnetic properties in CoFe/Pd multilayers - Bae, Joohyung; Kim, Hyung-jun; Chang, Joonyeon; Han, Suk Hee; Koo, Hyun Cheol; Lim, Sang Ho (KOREAN PHYSICAL SOC, 2012)
CoFe/Pd multilayers overcome the shape anisotropy and clearly show perpendicular magnetization. The thickness of the Pd buffer layer determines the coerciviy of the multilayer without reducing the magnetic moment. While the coercivity is 0.18 kOe without a buffer layer, the coercivity becomes 0.93 kOe with a 20 nm buffer layer. The coercivity linearly increases with increasing thickness of the buffer layer. When the buffer thickness is increased, the surface of the multilayer becomes rougher, which induces pinning site and increases the coercivity. The CoFe/Pd multilayer with a Au buffer layer has a larger coercivity than that with a Pd buffer layer because the Au buffer layer has a much rougher surface.
Keywords: PERPENDICULAR-ANISOTROPY; CO/AU MULTILAYERS; PD/CO MULTILAYERS; CO/PT MULTILAYERS; MICROSTRUCTURE; MECHANISM